In Situ Hydrodeoxygenation of Lignin-Derived Phenols With Synergistic Effect Between the Bimetal and Nb2O5 Support - Tong, Le; Cai, Bo; Zhang, Ronghua; Feng, Junfeng; Pan, Hui (Frontiers in Energy Research, 2021)
This work prepared the Nb2O5 supported bimetallic catalysts with impregnation method applied for the in-situ hydrogenation of guaiacol. Guaiacol can be effectively transformed into cyclohexanol over different bimetallic catalysts catalyst using alcohol as hydrogen donor. Meanwhile, the effects of different hydrogen donors such as isopropanol, sec-pentanol and ethylene glycol, on in-situ hydrogenation of guaiacol were investigated in detail, and the results shown that isopropanol is the best hydrogen supply solvent. Then, the dependence of Ni-Mn/Nb2O5 properties on metal loading, reaction time, reaction temperature and reaction pressure were studied for the in-situ hydrogenation of guaiacol by using isopropanol as hydrogen donor. Guaiacol can be completely converted and the yield of cyclohexanol reached 71.8% over Ni-Mn/Nb2O5 with isopropanol as hydrogen donor at 200 ℃ for 5 h. The structures and characteristic of better catalytic properties catalyst as Ni-Mn/Nb2O5 was determined by BET, NH3-TPD, XRD, XPS, SEM and TEM, the results indicated the particle size of metal was small (approximately 10 nm), the metal particles are finely dispersed in the whole support. Therefore, large number of medium acid sites were generated on the 10Ni-10Mn/Nb2O5 with large specific surface area, which could increase the interface between the metal and the support and may be beneficial to the hydrodeoxygenation of guaiacol